The impact of maternal obesity and race/ethnicity on perinatal outcomes: independent and joint effects - Snowden, Jonathan M (Obesity (Silver Spring), 2016)
OBJECTIVE: We characterized independent and joint impacts of maternal race/ethnicity and obesity on adverse birth outcomes, including preeclampsia, low birthweight (LBW), and macrosomia. METHODS: Retrospective cohort study of all 2007 California births using vital records and claims data. Maternal race/ethnicity and maternal BMI were the key exposures; we analyzed their independent and joint impact on outcomes using regression models. RESULTS: Racial/ethnic minority women of normal weight generally had higher risk as compared to white women of normal weight (e.g., African-American women, preeclampsia aOR, 1.60, 95% CI: 1.48 – 1.74, versus white women). However, elevated BMI did not usually confer additional risk (e.g., preeclampsia aOR comparing African-American women with morbid obesity to white women with morbid obesity; 1.17, 95% CI: 0.89 – 1.54). Obesity was a risk factor for LBW only among white women (morbid obesity aOR, 95% CI: 1.24, 1.04 – 1.49, versus white women of normal weight), and not among racial/ethnic minority women (e.g., African-American women, 0.95, 0.83 – 1.08). CONCLUSIONS: These findings add nuance to our understanding of the interplay between maternal race/ethnicity, BMI, and perinatal outcomes. While the BMI/adverse outcome gradient appears weaker in racial/ethnic minority women, this reflects the overall risk increase in racial/ethnic minority women of all body sizes.